Сорбційне очищення мінералізованих підземних вод від сполук урану з використанням піларованих глин - Ковальчук, І.А.; Пилипенко, І.В.; Корнілович, Б.Ю.; Бащак, О.Є. (Доповіді НАН України, 2019)
Досліджено закономірності сорбційного вилучення сполук урану(VI) з мінералізованих підземних вод. Встановлено, що синтезовані зразки пілар-глин мають значно кращі сорбційні властивості щодо вилучення урану
з мінералізованих розчинів порівняно з природними глинами. Показано, що у мінералізованих водах уран(VI)
знаходиться переважно в аніонній формі, а саме у вигляді карбонатних комплексів, які більш селективно вилучаються зразками пілар-бентоніту. За ефективністю вилучення аніонних форм урану з мінералізованих
вод пілар-бентоніти можна розмістити в ряд Ti > Fe > Zr > Al. Исследованы закономерности сорбционного извлечения соединений урана(VI) из минерализованных
подземных вод. Установлено, что синтезированные образцы пилар-глин имеют значительно лучшие сорбционные свойства по извлечению урана из минерализованных растворов по сравнению с природными
глинами. Показано, что в минерализованных водах уран(VI) находится преимущественно в анионной
форме, а именно в виде карбонатных комплексов, которые более селективно извлекаются образцами пилар-бентонита. По эффективности извлечения анионных форм урана из минерализованных вод пилар-бентониты можно разместить в ряд Ti> Fe> Zr> Al. The removal of uranium (VI) from mineralized groundwaters by the adsorption onto pillared-bentonites is
investigated. Various complexes of U(VI) in mineralized waters are examined. It has been shown that, in mineralized
groundwaters, anionic carbonate complexes of U(VI) are selectively removed by samples of pillaredbentonite.
Adsorption isotherms are obtained at pH 7.2 and an uranium concentration of 10—100 mg/l. The
order of extracting anionic forms of uranium by pillared-bentonites is Ti > Fe > Zr> Al indicating that the
Ti-pillared-bentonite form is the most effective in the removal of U(VI) from mineralized groundwaters. The
uranium sorption data are fitted by the Langmuir and Freundlich equilibrium models to obtain the characteristic
parameters of each model. According to the evaluation using the Langmuir model, the maximum sorption
capacity of uranium (VI) ions onto Ti-pillared-bentonite is 36.57 mg/g under the ratio of solid to liquid
500 in 1 h. The results suggest that pillared-bentonites are suitable materials for the preconcentration and
solidification of uranium (VI) species from mineralized groundwaters.